PERSONAL HATRIDITY, SIN AND REVENGE MOTIVES (International Conference on Education, Psychology and Humanities, 2026)
This article analyzes the concepts of personal enmity, guilt, and revenge, which are considered cornerstones in detective works and serve as motives for committing crimes, based on the works "Murder on the Eastern Express" by Agatha Christie, who left an indelible mark on English literature and is considered the queen of detective fiction, and "Chayongul," written by Khurshid Dostmuhammad, a representative of Uzbek literature. It is worth noting how important the article is in social life, and in this regard, one of the English reviewers, Chesternon, says: "The detective story is the normal recreation of noble minds" - that is, "A detective work is a natural recreation for people of high thinking." In general, these two detective works reveal how the concepts of truth, crime, and punishment are accepted and interpreted in two different societies. After all, in a good crime novel, it is not the detective who is more interesting, but the society he studies.
Keywords: Crime, Punishment, Society, Conscience, Revenge, Hatred, Enmity, Victim, Criminal, Tragedy, Social, Motivation, Murder, Victim, Justice, Detective, Exposure, Conviction, Collective punishment, Evil, Instinct, Voice of Conscience, pangs of conscience.